Beneficiaries’ Participatory Planning as a Strategy for Effective Project Implementation: A Case of Rwanda Tubura Project - Amutukundire, Margret (International Journal of Entrepreneurship and Project Management, 2025)
Purpose: Engaging local stakeholders is an important part of development work because it makes sure that the necessities and concerns of the local community are thought about and dealt with. Beneficiaries provide ideas during the planning phase of any project, and others add technical skills during the execution phase. The general objective of this study was to assess the effect of beneficiaries’ participatory planning as a strategy for effective implementation of Rwanda Tubura Project. The specific objectives were to establish the effect of beneficiaries in project planning on effective implementation of Rwanda Tubura Project, assess the effect of beneficiaries in decision making on effective implementation of Rwanda Tubura Project and investigate the effect of beneficiaries’ engagement on effective implementation of Rwanda Tubura Project. Methodology: Target population of this study was 217 project staff of Rwanda Tubura Project including project coordinators, administrative staff and project mentors. The Solvin formula was employed for sample size determination due to its straightforward and practical approach. Utilizing this formula with the given dataset resulted in a sample size of 141. Cluster sampling entails the selection of participant groups, referred to as clusters, from the overall population. The study utilized the following instruments for data collection: a survey, interviews, and a review of relevant documents. To conduct data analysis, the researcher employed the Statistical Package for Social Sciences (SPSS) statistical methodology. Findings: The coefficient of multiple determination (R-squared) was 0.671, signifying that approximately 67.1% of the variability in the dependent variable (effective implementation of Rwanda Tubura project) is explained by the combination of these predictors (beneficiaries’ engagement, decision making, and project planning). This indicates a strong correlation between the predictors and the dependent variable. Project planning (β=0.257, t= 3.073, p=0.003), Decision making (β=0.383, t= 4.878, p=0.000), and Beneficiaries’ engagement (β=0.254, t= 3.243, p=0.002) indicate that for every one-unit increase in these variables, there is a corresponding increase in the effective implementation of Rwanda Tubura project. Furthermore, the Significance values (Sig. 0.003, 0.000, 0.002) associated with beneficiaries’ participatory planning as strategy variables were all notably below the typical significance level (0.05), demonstrating their strong statistical significance and emphasizing their significant roles in contributing to the effective implementation of Rwanda Tubura project. Unique Contribution to Theory, Practice and Policy: Theoretical framework of this study concentrated on three theory namely participatory development theory, stakeholder theory and goal setting theory. Rwanda Tubura Project recommended to adapt effective implementation, strengthen project planning with comprehensive risk assessments and adaptive alignment. Also, Rwanda Tubura Project should establish a structured feedback mechanism for inclusive planning. Moreover, Rwanda Tubura Project should delegate decision-making authority to enhance on-the-ground responsiveness and efficiency. Rwanda Tubura Project should implement strong and continuous feedback mechanisms to assess beneficiary needs and create direct involvement platforms for beneficiaries in decision-making.